2006
DOI: 10.1134/s0006297906120091
|View full text |Cite
|
Sign up to set email alerts
|

DNA-methyltransferase SsoII as a bifunctional protein: Features of the interaction with the promoter region of SsoII restriction-modification genes

Abstract: DNA duplexes bearing an aldehyde group at the 2'-position of the sugar moiety were used for affinity modification of (cytosine-5)-DNA methyltransferase SsoII. It is shown that lysine residues of M.SsoII N-terminal region are located in proximity to DNA sugar-phosphate backbone of a regulatory sequence of promoter region of SsoII restriction-modification enzyme coding genes. The ability of the two M.SsoII subunits to interact with DNA regulatory sequence has been demonstrated by affinity modification using DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…After formation of the M.SsoII complex with the sets of DNA fragments containing the regulatory site ( 162reg-1 and 162reg-2 ), two types of DNA–protein complexes formed ( С1 and С2 , see above). There was much more complex C2 than complex C1 , just as in Figure 3 , pointing to high cooperativity of M.SsoII binding to the regulatory site in accordance with our earlier data when M.SsoII was cross-linked to DNA duplexes containing a reactive group at the regulatory site [ 67 ]. Complexes C2 showed significant differences in the electrophoretic mobility depending on the position of the regulatory site ( Figure 4 A).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…After formation of the M.SsoII complex with the sets of DNA fragments containing the regulatory site ( 162reg-1 and 162reg-2 ), two types of DNA–protein complexes formed ( С1 and С2 , see above). There was much more complex C2 than complex C1 , just as in Figure 3 , pointing to high cooperativity of M.SsoII binding to the regulatory site in accordance with our earlier data when M.SsoII was cross-linked to DNA duplexes containing a reactive group at the regulatory site [ 67 ]. Complexes C2 showed significant differences in the electrophoretic mobility depending on the position of the regulatory site ( Figure 4 A).…”
Section: Resultssupporting
confidence: 89%
“…Because M.SsoII has two different DNA-binding sites located in two different domains, one can imagine a complex where an M.SsoII molecule would be bound simultaneously to the methylation site and to the regulatory site. Although such a complex was fixed in our previous work [ 67 ], where two synthetic DNA duplexes with reactive groups were covalently cross-linked to the protein, we have never detected this complex experimentally under physiological conditions. Moreover, we found that the presence of 60reg-1 in a reaction mixture significantly decreased the binding of M.SsoII to 60met in the presence of cofactor analogue AdoHcy (data not shown).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…However, the protein dimer can assemble the proper complex only when the DNA is long enough (60 bp and more) [39]. The 31-bp duplexes used in the present work allow to detect only the intermediate complex where one M.SsoII molecule binds to one DNA duplex -either to the "left" half or to the "right" half of the regulatory site [34] [70] [71]. These two complexes have equal molecular mass and therefore cannot be distinguished by EMSA.…”
Section: Methyltransferase Ssoii Interaction With the Tg-containing Dmentioning
confidence: 99%